2003
DOI: 10.1677/erc.0.0100153
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and mammary cancer: a short review.

Abstract: Melatonin is an indolic hormone produced mainly by the pineal gland. The former hypothesis of its possible role in mammary cancer development was based on the evidence that melatonin down-regulates some of the pituitary and gonadal hormones that control mammary gland development and which are also responsible for the growth of hormone-dependent mammary tumors. Furthermore, melatonin could act directly on tumoral cells, as a naturally occurring antiestrogen, thereby influencing their proliferative rate. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 41 publications
2
95
0
Order By: Relevance
“…Aromatase activity in breast cancer tissue is higher than in non-malignant breast tissue, resulting in an increased production of estrogen within breast tumors [129]. Melatonin inhibits the expression and activity of enzymes, such as P 450 aromatase, estrogen sulfatase, and 17β-hydroxysteroid dehydrogenase, involved in the synthesis and transformation of biologically active estrogens, thus behaving as a selective enzyme modulator [130,131]. Melatonin also inhibits the increased proliferation of MCF-7 breast cancer cells induced by testosterone [132].…”
Section: Estrogen Enzyme Modulator Actionmentioning
confidence: 99%
“…Aromatase activity in breast cancer tissue is higher than in non-malignant breast tissue, resulting in an increased production of estrogen within breast tumors [129]. Melatonin inhibits the expression and activity of enzymes, such as P 450 aromatase, estrogen sulfatase, and 17β-hydroxysteroid dehydrogenase, involved in the synthesis and transformation of biologically active estrogens, thus behaving as a selective enzyme modulator [130,131]. Melatonin also inhibits the increased proliferation of MCF-7 breast cancer cells induced by testosterone [132].…”
Section: Estrogen Enzyme Modulator Actionmentioning
confidence: 99%
“…It has been reported that melatonin inhibits tumour growth in a variety of in vivo and in vitro experimental models of neoplasia (Cos and Sánchez-Barceló, 2000a, b;Blask et al, 2002). The oncostatic actions of melatonin have been demonstrated at length on hormonedependent tumours and especially on oestrogen-dependent breast cancer (Sánchez-Barceló et al, 2003. Experimental manipulations activating the pineal gland, or the administration of melatonin, reduce the incidence and growth rate of chemically induced mammary tumours in rodents, while pinealectomy or situations which implicate a reduction of melatonin production usually stimulate mammary carcinogenesis (Cos and Sánchez-Barceló, 2000a, b;Cos et al, 2006a).…”
mentioning
confidence: 99%
“…19 Additionally, it can act as a naturally occurring antiestrogen. 19 Melatonin is also known to cause local effects in the brain parenchyma and its surroundings and can alter the vulnerability and permissiveness to tumor invasion. 18 Melatonin can also provide antitumor effects by decreasing cell proliferation and inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%